Latitudinal effect on mosquitoes' microbiota - Leibetseder, Melissa (Jihočeská univerzita, 2020)
The aim of this thesis was to find environmental influences on the microbiota of Cx. pipiens mosquito, while investigating the 16S ribosomal RNA composition of the samples, collected over different latitudes in Europe.
Latitudinal effect on mosquitoes' microbiota
Keywords: mosquito; Culex pipiens; microbiota; 16S rRNA gene; environmental; latitude; Wolbachia; mosquito; Culex pipiens; microbiota; 16S rRNA gene; environmental; latitude; Wolbachia